SUN’S POLAR MAGNETIC FIELD REVERSALS IN SOLAR CYCLE 24 - Pishkalo, M. I.; Leiko, U. M. (Одеські астрономічні публікації, 2016)
It is known that polar magnetic field of the Sun changes its sign at the maximum of solar cycle. These changes were called as polar field reversals. We investigated dynamics of high-latitude solar magnetic fields separately in northern and southern hemispheres. Solar polar field strength measurements from the Wilcox Solar Observatory and low-resolution synoptic magnetic maps from the SOLIS project and from Helioseismic and Magnetic Imager (HMI) onboard Solar Dynamics Observatory were used. We analyzed total magnetic flux at near-polar zones, starting from 55, 60, 65, 70, 75, 80 and 85 degrees of latitude, and found time points when the total magnetic flux changed its sign. It was concluded that total magnetic flux changed its sign at first at lower latitudes and finally near the poles. Single polar magnetic field reversal was found in the southern hemisphere. The northern hemisphere was characterized by three-fold magnetic field reversal. Polar magnetic field reversals finished in northern and southern hemispheres by CR 2150 and CR 2162, respectively.